BUILDING IMAGE AND DIFFERENTIATION THROUGH PRODUCT BRANDING: A CONCEPTUAL ANALYSIS OF THE ROLE OF USP AND EXPERIENCE BRANDING - Silvia Ekasari (CV. Adiba Aisha Amira, 2026)
This article conceptually examines the role of Unique Selling Proposition (USP) and experience branding in building image and differentiation through product branding. In the context of increasingly fierce market competition, brands can no longer rely solely on product attributes or price, but need to integrate unique selling points (USP) with a holistic consumer experience (experience branding). Analysis shows that USP functions as a cognitive pillar that highlights the rational differences of a product, thereby strengthening brand image and differentiating it from competitors. On the other hand, experience branding acts as an affective pillar that builds image and differentiation through a series of sensory, emotional, intellectual, and behavioural experiences that are consistent across all touchpoints. The combination of the two creates a more comprehensive, sustainable, and relevant product branding strategy in today's experience-oriented market.